STRUCTUR AND STEREOTYPE IN SHORT STORY “SELAMAT PAGI, TUAN MENTERI” KARYA RADHAR PANCA DAHANA - Yusep Ahmadi F (IKIP Siliwangi, 2018)
This research is motivated by the importance of reading and deep story analysis in an effort to train analytical and aesthetic ability. This study aims to determine the structure and stereotypes in the short story